2021
DOI: 10.2478/aiht-2021-72-3517
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear medicine staff exposure to ionising radiation in 18F-FDG PET/CT practice: a preliminary retrospective study

Abstract: This retrospective study provides an insight into the levels of radiation exposure of six nuclear medicine (NM) staff (four technologists and two nurses) performing routine diagnostic 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography-computed tomography (PET/CT) at the University Clinical Centre of the Republic of Srpska, Department of Nuclear Medicine and Thyroid Disorders, Banja Luka, Bosnia and Herzegovina. Data analysis included monthly staff exposure measured with personal thermoluminescent do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In the current study, the overall extremity occupational radiation exposure was well below the annual dose limit of 500 mSv. [5] Nevertheless, the Extremity occupational exposure was higher than previously published results by Pavičar et al [3] and Adliene et al [12] but it is lower than the results shown by Kaljevic et al [13] and other studies (Table 5). However, there was no statistically significant difference in workers' average annual effective dose.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…In the current study, the overall extremity occupational radiation exposure was well below the annual dose limit of 500 mSv. [5] Nevertheless, the Extremity occupational exposure was higher than previously published results by Pavičar et al [3] and Adliene et al [12] but it is lower than the results shown by Kaljevic et al [13] and other studies (Table 5). However, there was no statistically significant difference in workers' average annual effective dose.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, each hospital can assess the occupational radiation dose for radiology workers in their department. [3] -4.37 μSv 6.55 μSv -Saad et al [14] -38.77 μSv 59.6 μSv 203 μSv Khouqeer [15] 223 mSv ---Kaljevic et al [13] 266 mSv ---Wrzesien et al [16] >500 mSv ---mSv = millisievert.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chosen TLD material is TLD-100 (LiF: Mg Ti), consistent with the standard dosimetry material employed in our hospital. Moreover, the dose level used in this study, i.e., 1 mSv, is relevant to occupational dosimetry for staff working with PET cameras [14]. Notably, there is no prior publication known to us that explores similar conditions.…”
Section: Discussionmentioning
confidence: 99%